2009
DOI: 10.1007/s10558-009-9073-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dσ*/dt max, a Load Independent Index of Contractility, in the Canine

Abstract: The search for a load-independent index of myocardial contractility has been a focus for nearly 100 years. Nearly all of the parameters developed have yielded insight into cardiac function but their clinical utility has been limited. A new index, dsigma*/dt (max), has been proposed to be useful in the clinic. This parameter is expressed as the maximum time rate of change of the pressure normalized circumferential wall stress (sigma* = sigma ( theta )/P, where sigma ( theta ) is circumferential wall stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The variations in preload and afterload in the present study were equal to or significantly greater than those reported in the literature. Reports of preload increase from 6% to 24% by saline infusion and preload decrease from 10% to 32% by IVCO have been made 14,34,36,38,39 as compared to 49% and 30% in our study, respectively. Similarly, afterload increases varied from 16% to 70% by aorta occlusion (as compared to 70% in this study), while afterload decreases varied from 13% to 29% by nitroprusside or nitroglycerin (NTG) in the literature.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…The variations in preload and afterload in the present study were equal to or significantly greater than those reported in the literature. Reports of preload increase from 6% to 24% by saline infusion and preload decrease from 10% to 32% by IVCO have been made 14,34,36,38,39 as compared to 49% and 30% in our study, respectively. Similarly, afterload increases varied from 16% to 70% by aorta occlusion (as compared to 70% in this study), while afterload decreases varied from 13% to 29% by nitroprusside or nitroglycerin (NTG) in the literature.…”
Section: Discussionsupporting
confidence: 45%
“…Black et al 34 reported a preload-dependence of d*/ dt max in canines based on IVCO. This disagreement is likely multi-factorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed study is shown in the Appendix. However, its loading dependence is still debatable [60]. The heart can also be viewed as a mechatronic organ.…”
Section: Contractility Indices Based On Left Ventricular Modelingmentioning
confidence: 99%